Crisis in the Multilateral System: The United Nations Dilemma in the Fallout of Russia's Invasion of Ukraine - M Pasqa; Asep A. Sahid Gatara (UIN Sunan Gunung Djati, 2023)
The Russian invasion significantly impacted the multilateral system and global geopolitics order. This research examines the impact of an invasion on the international system ruled by the United Nations and the Security Council in resolving conflicts. This study uses a qualitative technique by utilizing primary and secondary data regarding the analysis of invasion's alignment with principles of sovereignty and territorial integrity, while also highlighting the limitations of the current multilateral system. The invasion could have a negative impact on the multilateral system and create dilemma for resolving conflicts. This has led to serious problems for the whole multilateral system and has made it harder to solve future conflicts through international teamwork. This study proposes an analysis to maintain the multilateral system and reform the Security Council by limiting veto power for better conflict prevention and resolution. The UN Security Council's decision-making and crisis response could be improved by managing the interests of permanent members' veto powers. By investigating the challenges and action solutions to reduce disputes, this study emphasizes the importance of UN members' collective efforts and commitment to maintaining global peace as a national interest and maintaining security in the modern world.